Drag reduction performance of riblets - Leong, Chao Jun (2019)
Drag reduction has always been a tough issue in fluid dynamics, and the fluid of interest in this study is air. Global energy problem has motivated researchers to develop different drag reduction methods, including mimicking and replicating biomimetic structures of natural objects such as riblet. Despite the fact that riblets with different sizes and geometries have been tested and studied, and drag reduction of up to 9% has been achieved, the knowledge on the optimum riblet size and geometry in air flow remains relatively limited. Hence, this study aims to provide greater insights into the optimization of riblet height, as well as to investigate the effectiveness and flow mechanism of a new riblet design which has been proven effective in water but not yet tested in air. A total of thirteen aluminum test pieces, including one control, was investigated in this study. In the first part of this study, a set of four V-shaped riblets was investigated in a closed-loop wind tunnel. The V-shaped riblets were designed with varying riblet heights in an attempt to identify the relationship between riblet heights and drag reduction. Although no direct relationship were observed for both riblet height and height-to-spacing (h/s) ratio with drag reduction, the experiment concluded that at a riblet spacing of 0.7mm, greater riblet height and h/s ratio will more than likely lead to greater drag reduction, specifically a riblet height greater than 0.26mm and an h/s ratio greater than 0.37. In the second part of this study, a set of eight space-V riblets (new riblet geometry) was examined. The space-V riblets were designed with both varying riblet heights and riblet interval widths. At a riblet spacing of 0.7mm, space-V riblets were proven to be more effective than V-shaped riblets in reducing air drag by achieving the maximum pressure drop reduction of 39.0% among all the riblets tested. Besides, the results of the space-V riblets with varying riblet heights also agreed with the conclusion from the first part of the study. For instance, space-V riblets with riblet height greater than 0.24mm and h/s ratio greater than 0.35 will likely bring about greater drag reduction.